2016
DOI: 10.3109/03639045.2015.1135936
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of mucoadhesive microemulsion for neuroprotective effect of ibuprofen following intranasal route in the MPTP mice model

Abstract: Findings of the investigation revealed that Ibuprofen through developed MMEI was shown to protect neurons against MPTP-induced injury in the Substantia nigra pars compacta (SNpc) and striatum and hence, could be a promising approach for brain targeting of Ibuprofen through intranasal route to treat PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The effects of the drug delivery system were evaluated on an acute SCI rat model by hindlimb motor function, histopathological evaluation, immunohistochemistry and the assessment of the level of the inflammatory cytokine (tumor necrosis factor alpha, TNF-α). Furthermore, ibuprofen was chosen as the biologically active carboxylic acids, which could surmount axon growth restrictions from myelin and proteoglycans and stimulate a significant neurite growth in the cultured dorsal root ganglion neurons [ 30 ]. It has a great potential in the synergetic effect treatment for spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the drug delivery system were evaluated on an acute SCI rat model by hindlimb motor function, histopathological evaluation, immunohistochemistry and the assessment of the level of the inflammatory cytokine (tumor necrosis factor alpha, TNF-α). Furthermore, ibuprofen was chosen as the biologically active carboxylic acids, which could surmount axon growth restrictions from myelin and proteoglycans and stimulate a significant neurite growth in the cultured dorsal root ganglion neurons [ 30 ]. It has a great potential in the synergetic effect treatment for spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the therapeutic potentiality of anti-inflammatory drugs, like minocycline, dexamethasone, ibuprofen, celecoxib, salicylic acid, etc., in the treatment of PD. [95][96][97][98]171 The application of nanovesicular carriers in delivery of these anti-inflammatory drugs has also been explored in recent times. 172,173 Not much progress has been observed in this arena; however, in one study dexamethasone-loaded CD163+ ligand-tagged liposomes were found to exhibit sustained delivery of the loaded cargo to the immune cell population in the brain of PD rodents, increased striatal DA content, ameliorated dopaminergic neuron loss in SN, and improved motor performances.…”
Section: Nanovesicle-aided Delivery Of Drugs Targeting Dopamine Deple...mentioning
confidence: 99%
“…), ,, MAO-B inhibitors (e.g., selegiline and rasagiline), , and COMT inhibitors (e.g., entacapone and tolcapone) have the potential to keep a raised level of dopamine in the brain and hence are recommended as adjunctive to L-DOPA therapy. Preclinical and clinical studies provided evidence of immense therapeutic benefits of neurotrophins (BDNF and GDNF), , antioxidants (vitamin E, CoQ10, mitoQ), ,, anti-inflammatory drugs (dexamethasone, ibuprofen, celecoxib, minocycline), α-synuclein inhibitors (anti-α-synuclein ASO, shRNA, aptamer, NPT200-11), , and compounds targeting the lysosome–proteosome dysfunction (ambroxol, nilotinib, Hsp therapy, beclin, and parkin gene therapy) in exhibiting anti-PD effects. Moreover, numerous phyto-compounds (curcumin, resveratrol, quercetin, 7,8-dihydroxyflavone, lycopene) ,, have also been extensively explored and have shown remarkable potential against PD.…”
Section: Present Day Anti-pd Therapeutic Considerations and Their Lim...mentioning
confidence: 99%
“…Florence et al [146] published the results of a study aiming at the formulation of an intranasal, mucoadhesive oil-water (O/W) microemulsion for nose-to-brain delivery of clobazam, an anticonvulsant benzodiazepine drug used for the treatment of different epilepsy types and applied in some psychiatric disorders manifesting with anxiety. The obtained microemulsion contained Capmul ® MCM as the oil phase and the combination of polyoxyethylene-6-caprylic and capric glycerides (Acconan ® CC6) and Tween ® 20 as the Mandal et al [145] investigated intranasal mucoadhesive microemulsion with ibuprofen as neuroprotective agent in Parkinson's disease. Capmul ® MCM, Accenon ® CC, and Transcutol ® were selected as oil, surfactant, and co-surfactant, respectively.…”
Section: Epilepsymentioning
confidence: 99%